G20 Success Has Positive Impact for Indonesian MSMEs - Bambang Yuniarto; Siti nur khovivah; Nasywaa saajidah; Ahmad Faisal Fadhilah; Mohamad Ali hasan (Pusat Publikasi Nusantara, 2022)
The G20 Summit, which this year will take place in Indonesia, namely in Bali, is the 17th meeting of the Group of 20 (G20). The Indonesian Presidency took place from 1 December 2021 until the Summit in the 4th Quarter of 2022. The G20 Summit itself is a major forum for international economic cooperation whose members are the countries with the largest economies in the world consisting of 19 countries and one European Union institution. By convening this meeting, it is estimated that domestic consumption will increase to 1.7 trillion and increase domestic GDP by 7.43 trillion. In addition, meetings in various cities will increase the enthusiasm of the tourism and service sectors as well as UMKM from the employment side. The G20 meeting is expected to absorb 33,000 workers in various sectors. This prediction will greatly excite the business world, especially for MSMEs, especially since there are special tax restrictions for UMKM. The Presidential held in Indonesia this year is a momentum for recovery from the economic and financial crisis due to the Covid-19 pandemic. This momentum must be utilized by local governments to serve as a promotional event for the world of tourism, especially regions that have special economic zones. When the tourism sector rises, it will have an impact on UMKM products that can be in demand in the market both on a national and international market scale, meaning that this G20 meeting has been successfully carried out and has a positive impact on UMKM players in Indonesia so that the economy in Indonesia can gradually recover. The holding of the G20 can contribute to an increase in foreign tourists up to 3.6 million tourists so that 600 to 700 thousand new jobs will be created in the culinary, fashion and craft sectors. Holding the G20 meeting in Bali itself can attract foreign tourists to collaborate in the field of UMKM products so that MSME products can be sold and sell well in international markets.